Material flow analysis of commercial fishing gears in Taiwan. (May 2023) - Su, Ching-Tuan; Schneider, Falk; Deshpande, Paritosh C.; Xiao, Hui-Ya; Su, Tien-An; Yen, Ning; Lin, Hsin-Tien
Abstract: Marine debris is an international environmental issue, and the growing amount of abandoned, lost, or otherwise discarded fishing gear (ALDFG) is a particular concern. Despite Taiwan's substantial fishing industry, there is a lack of comprehensive understanding of fishing gear. This work conducted a static material flow analysis to estimate the flows and the stocks of fishing gear in Taiwan in 2020, based on government statistics and interviews with fishing gears producing companies, fishermen, and recycling companies. Our findings reveal that the inflow, outflow, and stock of the fishing gears are 8, 846 t/a, 4, 271 t/a, and 4, 575 t/a, respectively. Only 36 % of end-of-life fishing gear is recycled, while the rest is incinerated or landfilled. Additionally, the stock comprises 27 % in use, 23 % in ports, and 50 % entering the ocean. These results underscore the need to increase recycling capacity, prevent loss in oceans, and promote repairs to extend the lifespan of fishing gear. Graphical abstract: Unlabelled Image Highlights: Fishing gear flow analysis in Taiwan shows low recycling and high ocean loss. Only 17 % of end-of-life fishing gear is recycled, rest is incinerated in Taiwan. Fishing gear stock in Taiwan: 27 % in use, 23 % in ports, 50 % enters ocean Need to increase recycling, prevent loss, and extend fishing gear lifespan Collaboration is crucial for sustainable fishing and reducing impact.